Human capital mismatch and innovation performance in high-technology enterprises: An analysis based on the micro-level perspective - Jiayan Huang; Tomas Baležentis; Shaowei Shen; Dalia Štreimikienė (Journal of Innovation & Knowledge (JIK), 2023)
Micro-level analysis of innovation performance has become increasingly crucial to innovative policy in the context of innovation-driven economies. A micro-influence mechanism of human capital mismatch is presented in this paper and analysed. This research utilises a sample of 2510 high-tech enterprises in Zhejiang Province, China, for 2020. The research reveals that high-tech enterprises' limited human capital is still severely mismatched, which significantly impedes innovation. The conclusion remains valid even after accounting for omitted variable bias and reverse causality. Considering the moderating effect of mismatch and innovation, the results of the study indicate that R&D investment, domestic and foreign talent are detrimental to innovation in the presence of human capital mismatch. Finally, the article concludes by pointing out that correcting human capital mismatch, clarifying relationships among factor structure, price mechanism, and innovation performance, as well as accumulating human capital, is crucial for stimulating the innovation vitality of high-tech enterprises.
Keywords: 650; High-tech enterprises; Human capital mismatch; Innovation performance; Moderating mechanism